2021
DOI: 10.3389/frvir.2021.648601
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Self-Representation and Consistency in Collaborative Virtual Environments

Abstract: This paper explores the impact of self-representation (full body Self Avatar vs. Just Controllers) in a Collaborate Virtual Environment (CVE) and the consistency of self-representation between the users. We conducted two studies: Study 1 between a confederate and a participant, Study 2 between two participants. In both studies, participants were asked to play a collaborative game, and we investigated the effect on trust with a questionnaire, money invested in a trust game, and performance data. Study 1 suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A study by Pan and Steed 15 showed that a virtual body representation enabled participants to complete tasks together faster compared to a no-body representation, based on enhanced trust. Collingwoode-Williams et al 16 further found that consistency of representation, where each participant was represented by an avatar, compared to at least one of them only represented by a representation of the hand-held controllers further enhanced trust.…”
Section: Social Presencementioning
confidence: 98%
“…A study by Pan and Steed 15 showed that a virtual body representation enabled participants to complete tasks together faster compared to a no-body representation, based on enhanced trust. Collingwoode-Williams et al 16 further found that consistency of representation, where each participant was represented by an avatar, compared to at least one of them only represented by a representation of the hand-held controllers further enhanced trust.…”
Section: Social Presencementioning
confidence: 98%
“…In cases where normality was rejected, we conducted the appropriate non-parametric test to validate our result. A similar method is also used in [4]. As for study 1 our sample size is considered extremely small (N < 10) where the normality test itself can be less robust, even when normality was not rejected, we took extra steps to validate our data using additional statistical parameters suggested in [6].…”
Section: Measurement and Data Analysismentioning
confidence: 99%
“…What makes this convenient access to virtual experiences even more compelling is the ability to express ourselves through our self-avatar, something that could be tailored to reflect our real-life personality and style, or in some cases, one which we desire. However, research on the relationship between self-avatar's level of realism and its psychological impact on the users has been inconclusive [4,17,28]. One of the challenges is that the level of avatar realism can be decomposed into two seemingly orthogonal yet intertwined factors: visual fidelity (appearance realism) and motion fidelity (behaviour realism) [5,26].…”
Section: Introductionmentioning
confidence: 99%
“…In the sci-fi novel and movie The Martian (Figure 2), the Earthian-Martian communication leveraged text-based interaction and signage through black-and-white images in a turn-taking approach. Similarly, people's communication can be characterized by some type of turn-taking and non-real-time interaction, e.g., ARCAXER 4 . As such, we have to consider these characteristics as the core consideration of designing the interplanetary Metaverse.…”
Section: Possibilities Of Earthian-martian Interactionmentioning
confidence: 99%
“…The representation of the avatar has a strong impact on social dynamics [4,14]. In the case of embodied avatars, users' representation in the metaverse goes beyond visuals.…”
Section: Conclusion and Grand Challengesmentioning
confidence: 99%